Education and Research Enhancement in Land Administration Sector at Kathmandu University - Ghimire, Subash (Journal on Geoinformatics, Nepal, 2017)
This paper aims to strengthen the existing education and research in Land Administration and draw attention of all national and international Land Administration community for their contributions to promote education and research in Land Administration in developing countries such as Nepal. This paper also deals with the challenges and opportunities in collaborative efforts made by KU and LMTC to become a leader in this sector. The cost effective and reliable information is necessary for effective public service delivery. The economic growth of any country involves the effective service delivery. This requires highly skilled and knowledgeable human resources and output oriented research. To make land administration education, a leader course in Nepal and also within the region in the future, KU has to overcome many challenges. Some challenges may be addressed in the national level but some require collaborations and cooperation from international level. Finally, Education and research in Land Administration sector helps to develop quality land administrational professionals which in turn may incorporate the entire South Asia region as a potential Land Administration market. KU is committed to develop a centre of excellence in Land Administration sector by providing quality education and research. Nepalese Journal on Geoinformatics, Vol. 14, 2015, Page: 14-17